Desulfurization Technology for Industrial Fuel Gases Using Natural Adsorption Materials - Iliya Iliev; Antonina Filimonova; Alena Vlasova; Ruzina Kamalieva; Hristo Beloev (Engineering Proceedings)
Fuel gas desulfurization is an important technological step toward achieving environmental neutrality in industrial production. The presence of sulfur compounds in fuel not only significantly increases the rate of corrosion processes, but also increases the amount of sulfur oxides in flue gases. Adsorption technologies are actively used to purify fuel. Materials that are mainly chosen as sorbents are determined by economic feasibility. These materials include bentonite clays. The paper presents an analysis of scientific works on the possible methods of using bentonite clays in industry. Due to its natural properties, this material has high adsorption properties. The authors present experimental laboratory studies to determine the adsorption efficiency of bentonite clay with a carbon substrate. Results on the adsorption capacity after regeneration of the composition are also presented. Based on the data obtained, the adsorption unit was calculated, and the process flow diagram was designed.